A Consistent Characteristic Boundary Condition for General Fluid Mixture and Its Implementation in a Preconditioning Scheme (Advances in Applied Mathematics and Mechanics, 2012)
Characteristic boundary conditions that are capable of handlinggeneral fluid mixtures flow at all flow speeds are developed.The formulation is based on fundamental thermodynamics theoriesincorporated into an efficient preconditioning scheme in aunified manner. Local one-dimensional inviscid (LODI) relations compatible to the preconditioning system are proposed to obtaininformation carried by incoming characteristic waves atboundaries accurately. The approach has been validated againsta variety of sample problems at a broad range of fluid statesand flow speeds. Both acoustic waves and hydrodynamic flowfeatures can pass through the boundaries of computationaldomain transparently without any unphysical reflection orspurious distortion. The approach can be reliably applied tofluid flows at extensive thermodynamic states and flow speedsin numerical simulations. Moreover, the use of the boundarycondition shows to improve the computational efficiency.